Integrating physician’s and patient’s interest before judging the efficiency of a diagnostic test - Shanmugam, Ram (International Journal of Research in Medical Sciences, 2019)
Background: Customarily, physicians utilize an efficient diagnostic test before confirming the illness to start a treatment procedure. In this process, physician’s seeks maximum possible sensitivity and specificity. On the contrary, patient wants maximum attainable positive and negative predictive values. A duality exists between both vital patient’s and physician’s interest and it helps to judge whether a diagnostic is superior. Methods: This article integrates physician’s and patient’s interest in a novel manner to judge a diagnostic test is efficient. This approach is seen to be optimal, according to illustrations. Results: The results based on expressions of this article in data on rotavirus, mammogram, post-surgery infection, opinion of two independent nurses about ear infection, whether a surgery contained cancer cells, whether a second surgery rectifies ruptures in breast gels, and whether the elder’s fall due to medications they consumed are all convincing that the integration works well. Conclusions: The new integrated metric, , susceptibility index, excessive risk, calibration index, and phi-coefficients of this article are supportive to that both the physician’s and patient’s interest together identify a superior diagnostic test.